Focus on Local Cultural Attraction in Increasing Tourist Visits In Central Java Tourism Villages - Masayu Endang Apriyanti; Heru Subiyantoro; Cicih Ratnasih (Journal Research of Social Science, Economics, and Management, 2023)
Indonesia is a country that has natural beauty that is rich in cultural and artistic diversity which can provide an increase in state income. In line with the development of the world of tourism in Indonesia, efforts have been made to display interesting things, such as bringing in tourists. Efforts that can bring in tourists include: maintaining the authenticity of the renovated building and promoting tourist objects as tourist attractions. In addition, the government can provide support for efforts to attract tourists to tourist objects such as providing a special selfie room for tourists taking pictures, thus developing tourism as an industry becomes easy to increase economic growth, namely by only exploiting natural beauty, arts, culture, and hospitality to address the balance of payments deficit it experienced. That is why many experts are worried and consider it crucial to have careful planning in tourism development. The consideration is based on the concern regarding tourism as an industry that is expected to spur economic growth in DTW (Tourist Destination Areas) or countries visited by tourists. So that balanced growth can be developed, and the number of tourist arrivals can continue to grow. The research focuses on planning local cultural attractions in increasing tourist visits in the Central Java region.